eCM 2004
DOI: 10.22203/ecm.v007a05
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microfocus- and Synchrotron X-ray Tomography for the Analysis of Osteointegration around Ti6Al4V Implants

Abstract: Micro-computed tomography (µCT) provides quantitative three-dimensional information of bone around titanium implants similar to classical histology. The study, based on an animal model, using cuboid-shaped biofunctionalised Ti6Al4V implants with surrounding bone after 4 weeks, is performed using 3 µCT-systems with X-ray tubes, one synchrotron-radiation-based µCT-system (SRµCT), and classical histology. Although the spatial resolution of the µCT-systems is comparable, only the results of SRµCT agree with result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 40 publications
3
65
0
Order By: Relevance
“…lCT has also been used to quantify the bone contact area (apposition) between a solid non-porous implant and adjacent bone [17]. It is important to note however, that the application of lCT to quantify bone growth within porous metal implants is markedly different from quantification of bone contact to a solid (non porous) implant surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…lCT has also been used to quantify the bone contact area (apposition) between a solid non-porous implant and adjacent bone [17]. It is important to note however, that the application of lCT to quantify bone growth within porous metal implants is markedly different from quantification of bone contact to a solid (non porous) implant surface.…”
Section: Introductionmentioning
confidence: 99%
“…This represents a significant problem for metallic foams as the pore diameters are typically between 50 and 400 lm [ 18]. Reconstructed volumes are also affected by different hardware-related imaging artefacts, such as beam hardening from polychromatic X-ray sources and the reminiscence of the detector, which may impair the visualization of bone within distance up to 200 lm from the metal surface [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…For hard tissue (bone) the relatively simple laboratory systems using bremsstrahlung are often well suited. But the quantitative analysis of bony tissue around Ti-explants already requires the monochromatic synchrotron radiation [1]. The microstructure or morphology of soft tissue and biological cells is much more difficult to visualize because the differences in absorption are extremely small.…”
Section: Abstract: Synchrotron Radiation Tomography Tissuementioning
confidence: 99%
“…
Keywords: 3D-image analysis, porous materials, characterizationIn materials' science, as well as in other research fields, the Euler number (or its density) is used as a characteristic describing the connectivity of the components (constituents) of a composite material or the pore space of a porous medium, see [1]. From a theoretical point of view the Euler number of a 3-dimensional set X in the Euclidean space is a basic quantity of integral geometry.
…”
mentioning
confidence: 99%
“…For example, in a recently published study, 89% matching in bone area measurements was observed comparing lCT slices with light microscopical sections [2]. On the other hand, metallic implants cause so-called streaking artifacts due to scattering of X-rays, which prevents an accurate evaluation of the interfacial bone-to-implant contact [3,4]. Although, the placement of an aluminum filter between detector and specimens can suppress this phenomenon, it cannot be completely avoided [2].…”
Section: Introductionmentioning
confidence: 99%